Transport Risk Identification and Assessment - Jaroslava Kubáňová; Iveta Kubasáková (Communications - Scientific letters of the University of Zilina, 2021)
The transport process is characterized by transport operations and the relationships between them, the route, the time of transport and the type of product transported. One of these parameters is the degree of risk associated with a possible disruption of the transport process. Therefore, this article aims to present the possibility of calculating the degree of risk on the selected transport route. The risk level is calculated on based on the actual risk incidents on the transport route.